Postoperative Cochlear Obliteration after Retrosigmoid Approach in Patients with Vestibular Schwannoma - Hedjrat, Alireza; Schwager, Konrad; Hofmann, Erich; Behr, Robert (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective Vestibular schwannomas (VSNs) account for the vast majority of lesions located in the cerebellopontine angle (CPA). The goals of VSN surgery are possible total tumor removal, intact facial nerve function, and preservation of cochlear nerve function. In cases of pre- or postoperative deafness, restoration of hearing with auditory brainstem implant (ABI) or cochlear implant (CI) is a promising treatment option with normally better results in CI than in ABI. The aim of this retrospective study is to evaluate cochlear ossification or obliteration secondary to a retrosigmoid approach, which is important for later CI, especially in single-sided deafness.Materials and Methods We retrospectively reviewed data from our suboccipital retrosigmoid operation database for the period from January 2008 to February 2015. A total of 65 patients with VSN could be analyzed retrospectively. The patient's data (age, gender, side of operation, tumor entities, and the duration of follow-up) were evaluated. The most recent T2-weigted MRI exams were taken into account for the evaluation of cochlea. To compare left and right sides, the coronal reformatted images were reconstructed in a symmetrical way.Results Twenty-two out of 65 (33%) patients had cochlear obliteration in our survey. The cochlear obliteration was more common in females (44 vs. 20% in males). The median follow-up was 28 months. The size and the intrameatal extension of tumors could not be considered as factors influencing the cochlear obliteration rate.According to our survey, 33% of suboccipital approaches manifested cochlear obliteration to some extent. It was more common in females. The intrameatal extension of tumors played statistically no role in the occurrence of postoperative cochlear obliteration. Whether the prohibition of cochlear ossification can be best achieved by retrosigmoid approaches, compared to other approaches to the CPA, or not could be a subject of future studies.
Keywords: vestibular schwannoma; CPA; tumor; cochlear obliteration; DRIVE-sequence; retrosigmoid approach; cochlear ossification; cochlear implant